CLIMBING GRAMMAR MOUNTAIN GAME AS A REINFORCING TECHNIQUE IN TEACHING EXPRESSING DAILY ACTIVITIES - Arista, Dian; ., Sudarsono; ., Surmiyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak : PenelitianinibertujuanuntukmengetahuiseberapaefektifClimmbing Grammar Mountain Game sebagaiteknikpenguatanpenguasaan Simple Present Tense dalamkalimatpositif, negative, danpertanyaan yang bersubjek orang ketigatunggal. Samplepenelitianiniadalahsiswakelas VA SDS KarunaSingkawang yang terdiridari 32 siswa.Studiiniadalahpra-eksperimental.Data dikumpulkanmelaluitestertulisdalambentukpilihanganda.Hasilanalisis data menyatakanefeksizenya (ES) adalah 0,67. Karena ES terletakdiantara 0.2 dan 0,8olehkarenaitudikategorikansebagaimodeart. Dengandemikian Climbing Grammar Mountain Game terbuktisebagaiteknik yang baikterutamauntukpengajaran Simple Present Tense dalammengungkapkankegiatansehari-hari. Kata kunci: Climbing Grammar Mountain Game Abstract :This research aims to investigatethe effective size of Climbing Grammar Mountain Game as a technique to reinforce the students mastery of Simple Present Tense in positive statement, negative statement, and question. The subject of this research is year-5 students; class VA of SDS KarunaSingkawang. This class consists of 32 students. This study was pre-experimental. The data were collected through written test in form of multiple choices. Based on the data analysis, the effect size ( ES ) is 0.67. Since it is between 0.2 and 0.8, the effect size is categorized as moderate. Therefore, Climbing Grammar Mountain Game is proved as an effective technique to reinforce the mastery of Simple Present Tense. Keywords: Climbing Grammar Mountain Game